An Experimental Analysis on the Effects of Stagger on the Aerodynamic Forces of Tandem Wings - Y Parlindungan; S Tobing (Institut Teknologi Bandung, 2020)
This study is inspired by the flapping motion of natural flyers: insects. Many insects have two pairs of wings referred as tandem wings. Literature review indicates that the effects of tandem wing are influenced by parameters such as stagger (the stream-wise distance between the aerodynamic center of the front and the rear airfoil), angle-of-attack and flow velocity. As a first stage, this study focuses on the effects of stagger (St) on the aerodynamic performance of tandem wings. A recent numerical study of stagger on tandem airfoils in turbulent flow (Re = 6000000) concluded that a larger stagger resulted in a decrease in lift force, and an increase in drag force. However, for laminar flow (Re = 2000), increasing the stagger was not found to be detrimental for aerodynamic performance. Another work also revealed that the maximum lift coefficient for a tandem configuration decreased with increasing stagger. The focus of this study is to perform an experimental analysis of tandem two-dimensional (2D) NACA 0012 airfoils. The two airfoils are set at the same angle-of-attack of 0° to 15° with 5° interval and three variations of stagger: 1c, 1.5c and 2c. The experiments are conducted using an open-loop-subsonic wind tunnel at a Reynolds number of 170000. The effects of St on the aerodynamic forces (lift and drag) are analyzed